Job Satisfaction Mediates the Effect of Job Characteristics on Organizational Commitment (Study on Employees of PT. Marga Yumma Adventure): English - Hidayat, Rachmat; Gede Supartha, I Wayan (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
Organizational commitment is a strong desire of employees to survive and be actively involved in the organization to achieve the goals of the organization. The purpose of this study was to determine the effect of job characteristics on organizational commitment mediated by job satisfaction. This research was conducted at PT. Marga Yumma Adventure . The total population and samples taken were 63 respondents using a saturated sampling technique. Data collection was carried out through questionnaires and interviews. The analysis technique used is descriptive analysis, path analysis and sobel test. Based on the results of the analysis it was found that job characteristics had a positive and significant effect on organizational commitment. Job characteristics have a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on organizational commitment. Job satisfaction significantly mediates the relationship between job characteristics and organizational commitment. This means that the better the employees understand the characteristics of their work, the greater their job satisfaction, so that their commitment to the organization will increase. This study provides evidence that the factors influencing organizational commitment are job satisfaction through job characteristics and raises practical implications for PT. Marga Yumma Adventure and other companies to be able to use this research as a learning reference.